Imaging findings of succinate dehydrogenase‐deficient renal cell carcinoma - Wenqin Liu; Guiwu Chen; Jiaxin Meng; Xiaomin Liao; Yuhuan Xie (Clinical Case Reports, 2023)
Key Clinical Message A 50‐year‐old man with a mass located in the left kidney was described by multimodal images, including ultrasonography, computed tomography, and magnetic resonance imaging. After surgical resection of the mass, pathological examination confirmed succinate dehydrogenase‐deficient renal cell carcinoma. Abstract Succinate dehydrogenase‐deficient renal cell carcinoma (SDH‐deficient RCC) is a malignant tumor in the kidney associated with the loss of mitochondrial enzyme II. Due to its rarity, SDH‐deficient RCC is frequently misdiagnosed. We present multimodal imaging and pathologic findings in a 50‐year‐old male with SDH‐deficient RCC.